2018
DOI: 10.1155/2018/3708409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myopia among Children Attending Pediatrics Ophthalmology Clinic at Ohud Hospital, Medina, Saudi Arabia

Abstract: Introduction Around half of the visually impaired population has uncorrected refractive errors (URE), and myopia constitutes a high proportion of them. URE should be screened and treated early to prevent long-term complications. The aim of this study was to determine the prevalence of myopia among all patients attending a pediatric outpatient clinic at Ohud Hospital in Medina, Saudi Arabia (KSA). Method This study was conducted using a convenience sample of all patients attending the clinic (1500 patients) age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
6
2
Order By: Relevance
“…In comparison to national studies, the prevalence of myopia in our study is much higher than that in primary school children in Qassim, Saudi Arabia (5.8%) and among children attending pediatric ophthalmology clinics in Al-Madinah (3.5%) [2,9]. Moreover, it is more prevalent than in a study conducted on kindergarten and primary school entrants in Riyadh (2.5%) [3].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In comparison to national studies, the prevalence of myopia in our study is much higher than that in primary school children in Qassim, Saudi Arabia (5.8%) and among children attending pediatric ophthalmology clinics in Al-Madinah (3.5%) [2,9]. Moreover, it is more prevalent than in a study conducted on kindergarten and primary school entrants in Riyadh (2.5%) [3].…”
Section: Discussioncontrasting
confidence: 75%
“…Many studies have been carried out to investigate various environmental variables that may have a role in the development of myopia. The results on the effect of near-work activities, such as reading or using hand-held technology, have been contradicting [6][7][8][9][10]. On the other hand, numerous studies have revealed that spending time outside has a detrimental and protective effect on myopia [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But Alemam et al found myopia was more prevalent in males. The behavioral differences of children in different regions may lead to these variations [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent optical condition affecting people of all ages is refractive errors. According to WHO 43% of vision problems are attributable to refractive errors 16 and about half of visually impaired folks have uncorrected refractive errors (URE) 17 .…”
Section: Introductionmentioning
confidence: 99%